2011
DOI: 10.1186/1746-1596-6-s1-s17
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in standards for collaborative Digital Anatomic Pathology

Abstract: ContextCollaborative Digital Anatomic Pathology refers to the use of information technology that supports the creation and sharing or exchange of information, including data and images, during the complex workflow performed in an Anatomic Pathology department from specimen reception to report transmission and exploitation. Collaborative Digital Anatomic Pathology can only be fully achieved using medical informatics standards. The goal of the international integrating the Healthcare Enterprise (IHE) initiative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
(21 reference statements)
0
24
0
Order By: Relevance
“…The main research was conducted in the following. IHE Anatomic Pathology has proposed an Anatomic Pathology Structured Report (APSR), based in HL7 Clinical Document Architecture (CDA) [1,2]. In this document, anatomic pathology observations (e.g., breast-specimen collection procedure) and the possible values (e.g., breast excision without wire-guided localization) have been coded using the PathLex coding system.…”
Section: Informatics Standards In Pathologymentioning
confidence: 99%
“…The main research was conducted in the following. IHE Anatomic Pathology has proposed an Anatomic Pathology Structured Report (APSR), based in HL7 Clinical Document Architecture (CDA) [1,2]. In this document, anatomic pathology observations (e.g., breast-specimen collection procedure) and the possible values (e.g., breast excision without wire-guided localization) have been coded using the PathLex coding system.…”
Section: Informatics Standards In Pathologymentioning
confidence: 99%
“…However, some urologists and pathologists may find electronic systems less convenient than paper, especially considering the time needed to set them up and train staff. Multiple groups have endeavored to define a common structured data format for oncologic pathology reporting 42,43 and templates from CAP are now widely used. Several studies have shown that using voice recognition technology shortened turnaround time while reducing transcription errors.…”
Section: Improving Efficiency Of Urologist–pathologist Interactionsmentioning
confidence: 99%
“…Numerous protocols have been developed to manage and exchange healthcare information, including the Digital Image Communications in Medicine (DICOM) [72]–[74] in radiology and Health Level Seven (HL7) [18], [73], [74] for clinical data. Nomenclature methods have also been developed to establish a lingua franca for the terminology in data exchange, including Logical Observation Identifier Names and Codes (LOINC) [32] and Unified Medical Language System (UMLS).…”
Section: Management Infrastructurementioning
confidence: 99%